PENGARUH PENGGUNAAN MEDIA KAHOOT PADA MATERI PENDAPATAN NASIONAL UNTUK MENINGKATKAN MINAT BELAJAR MAHASISWA - Mica Siar Meiriza; Pebri Andini; Khaalisah Maisuuna Rahman; Tata Khairina Daulay; Siti Aidilia Azzahra; Hizia; Chelsea Oktavia Purba; Amanda Talitha Fitri; Yusniar; Jenari Sembiring; Zulaika Syah putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using Kahoot as a learning media on students’ learning interest in national income material. This research employed a quantitative approach with an experimental method using a one-group pretest-posttest design. The subjects of this study were 27 students. Data were collected through questionnaires and tests in the form of pretest and posttest. Data analysis used descriptive and inferential analysis with a paired sample t-test and N-Gain calculation. The results showed that the average pretest score was 28.5, which was categorized as low. After the implementation of Kahoot, there was an increase in students’ learning interest and learning outcomes. The use of Kahoot in learning was able to enhance students’ activeness, engagement, and enthusiasm during the learning process. Therefore, Kahoot as a learning media has a positive effect on improving students’ learning interest in national income material.